Filmy edukacyjne z zakresu technologii informacyjno-komunikacyjnych (ICT) w kształceniu uniwersyteckim - Jędryczkowski, Jacek (Studia Edukacyjne, 2026)
The article discusses ways of producing educational films on information and communication technologies (ICT) for students who carry out projects and tasks independently and who are catching up on work missed due to absence. It also presents ways of distributing films using an educational YouTube channel and websites prepared for individual laboratory groups. This form of publication provided access to YouTube Analytics, which records all forms of interaction with the video material. The reports collected in this way enable the assessment of the viewership of educational materials and allow for the analysis of the learning strategies of students and Internet users in general. The article will present examples of research carried out in this way. It was found that the videos available on the channel were viewed over 1,832,022 times and watched for over 61,758 hours. It was observed that students of the University of Zielona Góra accounted for only 1.33% of views and 2.86% of viewing time. This means that the educational channel currently serves as a massive open online course, which justifies the need to create this type of content.